Determinants of interest rate spreads in Zimbabwe (2009-2012) - Mudzingwa, Nyasha Blessed (Midlands State University, 2014)
The study focused on the determinants of bank interest rate spreads in Zimbabwe’s commercial banking sector during the multiple currency period from 2009 to 2012. The study was based on the hypothesis that bank interest rate spreads are determined by banks specific factors and macro economic factors. Several theories including the Loanble funds, Liquidity preference, Loan pricing, Signaling arguments and Credit market theories were propounded to explain the determinants of interest rates and interest rate spread. A descriptive research design was chosen and is used to show trends and comparative analysis of interest rate spreads and other variables of interest. The design is also quite employable when there is a specific question for study and the methodologies to be done are already known which the case in this study was. An econometric model which employed panel data techniques to analyze the influence of bank specific and macroeconomic factors on bank spreads and the variables were chosen based on findings from both empirical and theoretical literature. The variables chosen were liquidity, operating costs, non-performing loans, growth in gross domestic product and inflation. Results obtained indicated that bank spreads are high in Zimbabwe and they are mostly driven by non-performing loans, growth in gross domestic product and inflation. The other variables which were liquidity and operating costs proved not to be significant in determining interest rate spreads. Foreign banks charged lower spreads than local banks in the same period. Lending rates were highly volatile as compared to deposit rates. The study recommends policies to increase competition, operational efficiency, coping foreign legislation, strengthening local banks, and improving international relations. Further studies were recommended in the areas of the impact of market specific factors in determining spreads in a stable environment, whereby regulatory policies don’t frequently change